AL-TA'ASSUF IN GOVERNMENT REGULATION NO. 45 OF 1990 ARTICLE 4 PARAGRAPH 2 - Novita Anggraeni; Ahmad Arief; Andi Muh. Taqiyuddin BN; Abu Sahman Nasim; Muh. Bambang Taufik (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2025)
The purpose of this research is to reveal the indicators of al-Ta'assuf in Government Regulation No. 45 of 1990 Article 4 paragraph 2 and legal solutions to al-Ta'assuf in Government Regulation No. 45 of 1990 Article 4 paragraph 2. This research is qualitative research, the type of research is library research. The data collection method used is literature study, with normative theological, juridical, and sociological approaches. The results showed that;1) The two indicators of al-ta'assuf in the use of rights have been used to analyze Government Regulation No. 45 of 1990 Article 4 paragraph 2. In accordance with the analysis of al-ta'assuf, Government Regulation No. 45 of 1990 Article 4 paragraph 2, should not conclude its provisions by prohibiting civil servant women as polygynous wives absolutely. Because the absolute prohibition will always be understood in any condition and however, without any conditions. 2) The legal solution to al-Ta'assuf in Government Regulation No. 45 of 1990 Article 4 paragraph 2, namely the government as the competent authority in establishing regulations, should pay attention to the greater good by considering the rights of civil servant women and children who are born later.